2013
DOI: 10.1093/nar/gkt440
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol binding alters human telomere G-quadruplex structure by conformational selection

Abstract: Polyethylene glycols (PEGs) are widely used to perturb the conformations of nucleic acids, including G-quadruplexes. The mechanism by which PEG alters G-quadruplex conformation is poorly understood. We describe here studies designed to determine how PEG and other co-solutes affect the conformation of the human telomeric quadruplex. Osmotic stress studies using acetonitrile and ethylene glycol show that conversion of the ‘hybrid’ conformation to an all-parallel ‘propeller’ conformation is accompanied by the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 81 publications
1
133
1
1
Order By: Relevance
“…Tellingly, hammerhead self-cleavage was not accelerated when using Ficoll as a crowder, and from this, the authors inferred that the excluded volume effects were minimal. PEG was also reported to directly alter DNA quadruplex conformation (22). By contrast, compartmentalization increased selfcleavage of a two-part hammerhead ribozyme, showing that co-localization can increase RNA interactions (23).…”
mentioning
confidence: 99%
“…Tellingly, hammerhead self-cleavage was not accelerated when using Ficoll as a crowder, and from this, the authors inferred that the excluded volume effects were minimal. PEG was also reported to directly alter DNA quadruplex conformation (22). By contrast, compartmentalization increased selfcleavage of a two-part hammerhead ribozyme, showing that co-localization can increase RNA interactions (23).…”
mentioning
confidence: 99%
“…Thus PEG is driving the equilibrium to the side of Conformer II with increasing concentrations as observed before with different G-rich sequences [22][23][24][25][26][27][28][29]31]. According to Chaires et al, this shift in equilibrium is due to conformational selection rather than excluded volume or crowding effects [31]. None the less, the high concentrations of PEG will slightly influence the activity of water which will contribute to overall conformational stability.…”
Section: Introductionmentioning
confidence: 59%
“…Thus, PEG 200 falls under the regime of preferential interaction rather than excluded volume. Further, a recent report suggests that PEG preferentially interacts with a particular quadruplex conformation and that excluded volume effects are negligible [31]. Although the presence of PEG in solution clearly influences the conformation and stability of a DNA quadruplex, referring to it as a crowding agent is not recommended [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the surface of a protein near the site of PEGylation is locally dehydrated [12]. Furthermore, PEG has been shown to interact specifically with the surface of a G-quartet by molecular modeling analysis [13]. Thus, it is possible that PEGylation of that DNA forms a G-quadruplex will cause dehydration during formation of G-quadruplex structure through specific interactions with a G-quartet surface.…”
Section: Archivos Dementioning
confidence: 99%